1999
DOI: 10.1002/(sici)1521-3773(19990419)38:8<1124::aid-anie1124>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

A Method for the Selection of Catalytic Activity Using Phage Display and Proximity Coupling

Abstract: Phage display has been used extensively for the selection of proteins with binding sites for ligands. Here, as illustrated with the example of DNA polymerase, the use of phage display for selection according to catalytic activity is described. Active enzymes are selected by binding of the reaction product P (see the scheme) cross-linked in the proximity of the enzyme E that catalyzed the reaction with the substrate S.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0
5

Year Published

2000
2000
2008
2008

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(50 citation statements)
references
References 13 publications
1
44
0
5
Order By: Relevance
“…Polymerases have been selected successfully for activity by phage display (9) and by complementation of a DNA polymerase I-deficient Escherichia coli strain (10). Careful screening of the complementing polymerase mutants yielded polymerases with a range of interesting properties such as altered fidelity (11).…”
mentioning
confidence: 99%
“…Polymerases have been selected successfully for activity by phage display (9) and by complementation of a DNA polymerase I-deficient Escherichia coli strain (10). Careful screening of the complementing polymerase mutants yielded polymerases with a range of interesting properties such as altered fidelity (11).…”
mentioning
confidence: 99%
“…For example, with water-in-oil emulsion technology (14), Holliger and coworkers (15) evolved DNA polymerases that were either more thermally stable or more resistant to an inhibitor. Winters and coworkers (16) demonstrated that phage pIII-displayed DNA polymerases could be isolated based on their activity-dependent modification of an attached substrate. However, the substrate was attached to the major phage coat protein, pVIII, raising the concern of cross-reactivity between a polymerase on one phage and a substrate attached to another phage.…”
mentioning
confidence: 99%
“…Only opal stop codon-containing clones were selected from the library, whereas, in their absence, almost exclusively chimeric gene fusions leading to a frameshift between the barnase and p3 genes were selected (unpublished data). Phage was prepared by using the helper phage KM13 (27), which encodes a trypsin-sensitive p3 mutant, to reduce contributions to infectivity from phage that do not display the fusion protein (28).…”
Section: Methodsmentioning
confidence: 99%